A Study on the Impact of the Covid-19 Pandemic on Student Affairs Practitioners in Zimbabwe - Mutambisi, Sebastian; Murasi, Dora Dorothy; Mazodze, Crispen (An Overview of Literature, Language and Education Research Vol. 9, 2025)
This article seeks to contribute to knowledge sharing with regard to the effect of the COVID-19 pandemic on student affairs practitioners and their practice in general. The World Health Organization (WHO) declared the novel coronavirus a Public Health Emergency of International Concern on 30 January 2020. The COVID-19 pandemic has had an unprecedented impact on faculty and student affairs practitioners which has changed the future of higher education worldwide. This study is informed by Kurt Lewin and John Potter’s change management models which outline how organisational change efforts can be planned, organised and managed. This reflective practitioner account looks into its impact on practitioners working in student affairs, some of which is not immediately visible, but unfortunately very significant and will surface in the medium and long term. There has been tremendous uncertainty for Student Affairs Practitioners as a result of disruption from familiar routines and unexpected disengagement with their clients, the students. The change management perspective and scholarship of practice were adopted as methods of observing how a department in a university deals with unplanned change. The findings showed that practitioners went through a rigorous change programme which helped them embrace the new normal. The study also showed that practitioners went through a process of loss of skills, isolation and separation from their work communities, grappled with new modes of presentation, loss of income for some and constrained resource availability. The study concluded that the Covid-19 pandemic impacted practitioners negatively at the case university as new skills were required, practitioners were required to adjust to new work arrangements, lost income, suffered mental health problems and faced resource constraints. Training and development, social media, employee support systems and employee incentives were catalysts in the early adoption of change.